Preference reversals in ethicality judgments of medical treatments - Benjamin A. Lemli; Justin F. Landy (PLoS ONE, 2025)
In medical ethics, there is often a tradeoff between maximizing treatment efficacy and alleviating patient suffering. We adapt methods from consumer behavior research to examine whether ethicality judgments of medical treatments that vary on these dimensions exhibit preference reversals across tasks and evaluation modes. Specifically, we present participants with pairs of treatments that symmetrically dominate one another: one is more effective, while the other improves patients’ quality-of-life. Across three studies (total N = 500), we demonstrate classic preference reversals in lay medical ethics judgments: participants prioritized efficacy over quality-of-life concerns in matching tasks more than choice and rating tasks, in between-subjects (Study 1) and within-subjects (Study 2) designs, and in joint evaluation more than sequential evaluation (Study 3). We interpret these findings in light of previous research on preference reversals in other domains and discuss implications for healthcare and moral psychology.